EpiReumaPt- the study of rheumatic and musculoskeletal diseases in Portugal - Maria Rodrigues, Ana (2015)
Rheumatic and musculoskeletal diseases (RMD) are prevalent and leading causes of disability and consumption of healthcare and social resources. EpiReumaPt is a national population-based survey developed by the Portuguese Society of Rheumatology that aimed to estimate the prevalence of RMDs and determine their impact on function, quality of life, mental health and use of healthcare resources. This article describes in detail the design, methodology and planned analyses of EpiReumaPt. Recruitment started in September 2011 and finished in December 2013. This study involved a three-stage approach. The first step was a face-to-face survey performed by trained interviewers at the household of 10,661 subjects who where randomly selected by a stratified multistage sampling. A highly sensitive screening questionnaire for RMDs was used. Secondly, participants who screened positive (64%) for at least one RMD as well as 20% of individuals with a negative screening were invited for assessment by a rheumatologist. In total, 3,877 subjects participated in this second phase, where they were also invited to donate a blood sample to be stored at the Biobanco-IMM. History and physical examination, followed by appropriate laboratory and imaging tests were performed. At the end of the visit, the rheumatologist established a diagnosis. Finally, a team of three experienced rheumatologists reviewed all the clinical data and defined the diagnoses according to previously validated criteria. The EpiReumaPt dataset, containing data from several questionnaires, various clinical measurements and information from laboratory and imaging tests, comprises an invaluable asset for research. The large amount of information collected from each participant and the large number of participants, with a wide age range covering and being representative of the adults from the entire country, makes EpiReumaPt the largest study of RMDs performed in Portugal.